Gold versus Palladium: A Regioselective Cycloisomerization of Aromatic Enynes. Issue 17 (14th November 2013) - Aziz, Jessy; Frison, Gilles; Le Menez, Patrick; Brion, Jean‐Daniel; Hamze, Abdallah; Alami, Mouad
Abstract Aromatic enynes can be transformed into arylnaphthalenes or benzofulvenes depending on the reaction conditions. Under gold(I) catalysis, exclusive or major 6‐endo‐dig cyclization took place leading to arylnaphthalenes. However, a catalytic system based on palladium iodide/1, 3‐bis(diphenylphosphino)propane, in the presence of cesium carbonate as a base was necessary to furnish exclusively 5‐exo‐dig cyclization pattern, regardless of the electronic effects of the substituents. In the latter transformation, a mechanistic study (kinetic isotopic effect, density functional theory) involving a CH activation is suggested for the exclusive formation of benzofulvenes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>